Wind Energy Meteorology Atmospheric Physics for Wind Power Generation - Emeis, Stefan (Green Energy and Technology, 2013)
This book is intended to give an introduction into the meteorological boundary conditions for power generation from the wind, onshore and offshore. It is to provide reliable meteorological information for the planning and running of this important kind of renewable energy. This includes the derivation of wind laws and wind profile descriptions, especially those above the logarithmic surface layer. Winds over complex terrain and nocturnal low-level jets are considered as well. A special chapter is devoted to the efficiency of large wind parks and their wakes.